Additional DNA barcodes confirm recent morphological species concepts and synonymies in Callomyia Meigen (Diptera: Platypezidae) - Cumming, Jeffrey M.; Cumming, Heather J. (Zootaxa, 2019)
Cumming & Wheeler (2016) revised the Nearctic species of the sexually dimorphic flat-footed fly genus Callomyia Meigen (Callomyiinae) recognizing 10 Nearctic species, including three newly described taxa, namely C. argentea Cumming, C. arnaudi Cumming, and C. browni Cumming. They also described the unknown female of C. velutina Johnson and proposed three new synonymies associating species previously described from one sex only with others described from the opposite sex (Kessel 1948; Kessel & Buegler 1972). Callomyia cleta Kessel was considered a junior synonym of C. calla Kessel, C. clara Kessel was considered a junior synonym of C. corvina Kessel, and C. liardia Kessel & Buegler was synonymized with C. proxima Johnson.